Case report: Hypoadrenocorticism crisis complicated by non-cardiogenic pulmonary edema in a dog - Paulin, Mathieu V.; Snead, Elisabeth C. (Frontiers in Veterinary Science, 2022)
A 6-year-old castrated male Labradoodle was referred in uncompensated hypovolemic shock, with a 72-hour history of lethargy, vomiting and diarrhea that had acutely worsened with subsequent development of profuse hemorrhagic diarrhea in the last 24 hours after a visit to the groomer. In most respects this case was classic for a patient with a primary hypoadrenocortical crisis. After initial attempts to address hypovolemia and refractory hypotension, no clinical improvement was seen, and the respiratory rate had increased acutely to 80 bpm with crackles detected on thoracic auscultation and serosanguineous fluid began draining from the nose and mouth. An arterial blood gas sample while breathing room air revealed moderate hypoxemia (PaO2 59.9: RI 95-100 mmHg), an elevated alveolar-arterial (A-a) gradient at 54.7 (RI < 15 mmHg) and a PaO2:FiO2 ratio of 285 mmHg. Thoracic radiographs revealed severe bilateral alveolar lung pattern largely limited to the perihilar and caudodorsal lung fields. The radiographic findings, along with signs of ongoing hypovolemia, the lack of evidence of typical long-standing acquired cardiac disease, and the rapid resolution of the pulmonary edema without the need for diuretics or long-term cardiac medications supported noncardiogenic pulmonary edema. The proposed cause of the noncardiogenic pulmonary edema was speculated to be neurogenically mediated. Oxygen supplementation along with mineralocorticoid and glucocorticoid replacement therapy was sufficient for the management of the non-cardiogenic pulmonary edema in this case.